(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Postcovoid syndrome is currently considered as a multifactorial condition accompanied by long-term persistent disorders of various internal organs and systems. After SARS-CoV-2 infection, a significant proportion of patients develop visceral changes in their cardiovascular, hepatobiliary, metabolic, and coagulation patterns due to systemic inflammation, endothelial dysfunction, and immune response disorders.